2020
DOI: 10.1534/genetics.120.303330
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Genetic Contributions to Imperfect wMel-Like Wolbachia Transmission and Frequency Variation

Abstract: Maternally transmitted Wolbachia bacteria infect about half of all insect species. They usually show imperfect maternal transmission and often produce cytoplasmic incompatibility (CI). Irrespective of CI, Wolbachia frequencies tend to increase when rare only if they benefit host fitness. Several Wolbachia, including wMel that infects Drosophila melanogaster cause weak or no CI and persist at intermediate frequencies. On the island of São Tomé off West Africa, the frequencies of wMel-like Wolbachia infecting D.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(78 citation statements)
references
References 99 publications
5
73
0
Order By: Relevance
“…Our results add to mounting literature showing that temperature is an important abiotic factor mediating interactions between Wolbachia and their hosts (112). Wolbachia titer seems to be especially sensitive to temperature (42,58,60,61,63,(113)(114)(115)(116). Our 24-h temperature shift experiments suggest that Wolbachia titer can change over very short time periods due to environmental conditions.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Our results add to mounting literature showing that temperature is an important abiotic factor mediating interactions between Wolbachia and their hosts (112). Wolbachia titer seems to be especially sensitive to temperature (42,58,60,61,63,(113)(114)(115)(116). Our 24-h temperature shift experiments suggest that Wolbachia titer can change over very short time periods due to environmental conditions.…”
Section: Discussionsupporting
confidence: 76%
“…Increased Wolbachia titer in males is unlikely to affect rates of maternal Wolbachia transmission, but perhaps temperature-associated titer increases could alter the strength of cytoplasmic incompatibility caused by males infected with wSh or wTei (85,87,95,106). Other studies have also reported male-biased effects on Wolbachia titer (42,62,107); for example, our own work demonstrated that maternal transmission of wYak to sons is more efficient than to daughters when D. yakuba mothers are reared in cold 20°C conditions (42).…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations